Pemetaan Penyandang Masalah Kesejahteraan Sosial menggunakan Sistem Informasi Geografis di Kota Bogor - Claus Asido Pioraja; Fatwa Ramdani; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Bogor is one of the cities with a fairly high population growth in West Java Province. According to data from the Central Bureau of Statistics of the city of Bogor (BPS) in 2020 the city of Bogor has 1,126,927 inhabitants. The city of Bogor has increased by 1.33% compared to 2019. By looking at the trend of population development in the city of Bogor which continues to increase, it can be predicted that the number of people with social welfare problem will continue to increase. Some decision is needed to use and maximize usage of existing data for better understanding of the problem, therefore the City Government can make better efforts to reduce people with social welfare in Bogor. Geographic Information System (GIS) can be a useful tool to help visualizing the population condition of an area to describe the level of welfare of its population. GIS can also provide information in the form of thematic maps so that the condition of an area towards poverty can be presented in the form of digital map visualization and can make it easier to understand the information presented. This GIS shows existing data of people with social welfare and combine it with the existing geographic features. This social welfare data will be displayed with a Bubble Chart type of visualization. This type was chosen because it can clearly visualize the comparison of data for each sub-district.